2003
DOI: 10.1200/jco.2003.12.120
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Pharmacokinetic and Pharmacodynamic Study of Recombinant Human Endostatin in Patients With Advanced Solid Tumors

Abstract: Endostatin given daily as a 1-hour intravenous infusion was well tolerated without dose-limiting toxicity at doses up to 300 mg/m2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(133 citation statements)
references
References 43 publications
3
130
0
Order By: Relevance
“…Such antibodies have been described in a clinical trial of recombinant human endostatin in which they were not associated with changes in endostatin pharmacokinetic (Thomas et al, 2003). However, the goal of this phase I clinical trial was not to assess clinical efficacy, and no response was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Such antibodies have been described in a clinical trial of recombinant human endostatin in which they were not associated with changes in endostatin pharmacokinetic (Thomas et al, 2003). However, the goal of this phase I clinical trial was not to assess clinical efficacy, and no response was observed.…”
Section: Discussionmentioning
confidence: 99%
“…All three phase I studies utilised radiological and biopsy-based indicators of tumour angiogenesis to assess BED. Thomas et al (2003) failed to demonstrate any significant changes by in vivo imaging with dynamic CT (marker of microvessel density), dynamic MRI (marker of tumour blood flow) or [ 18 F]FDG PET (measure of tumour glucose metabolism). No changes in microvessel density, endothelial cell apoptosis, proliferation or vessel maturity were seen in paired pre-and 8-week post-treatment tumour biopsies from patients in this study although only eight sample pairs were available for analysis.…”
Section: Clinical Studiesmentioning
confidence: 95%
“…Although pharmacokinetic data were linear and analysis of serumisolated endostatin in one phase I study (Thomas et al, 2003) did not demonstrate extensive proteolytic degradation, small shifts in mass spectrometry profiles were noted that could be consistent with limited terminal proteolytic cleavage. Of note, no in vitro activity could be demonstrated for re-isolated endostatin in any of the three studies.…”
Section: Immunogenicity Intravascular Proteolysis and A Potential Plmentioning
confidence: 97%
See 1 more Smart Citation
“…Use of endostatin in clinical trials in cancer therapy has been hampered by difficulties in protein production in large quantities, loss of biologic activity during long-term storage, and cumbersome daily administration requirements. Three phase I clinical trials and a recently reported phase II clinical trial of endostatin in patients with advanced neuroendocrine tumours have not demonstrated anti-tumour activity (Eder et al, 2002;Herbst et al, 2002;Thomas et al, 2003;Kulke et al, 2006). In the phase II study, steady-state trough levels were below the target therapeutic range.…”
mentioning
confidence: 97%